2020
DOI: 10.1038/s41598-020-77833-1
|View full text |Cite
|
Sign up to set email alerts
|

Visual hallucinations in Parkinson’s disease are associated with thinning of the inner retina

Abstract: Visual hallucinations (VH) are common in patients with Parkinson’s disease (PD), yet the underlying pathophysiological mechanisms are still unclear. We aimed to explore the association of the presence of VH with inner retinal thinning and, secondarily, with visual acuity. To this end, we included 40 PD patients in this exploratory study, of whom 14 had VH, and 22 age- and sex-matched healthy controls. All participants were interviewed for the presence of VH by a neurologist specialized in movement disorders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In particular, the frontostriatal syndrome does not predict PDD, whereas PC syndrome does. 42 43 In this context, some biomarkers could help us to understand the origin of these complications in patients with PD, 30 41 44 45 46 but we did not detect differences in the SB analysis. Although previous studies found that SCC were an independent predictor of MCI development in CN patients with PD, 10 11 47 only persistent SCC were associated with CI in our study when no other covariates were considered.…”
Section: Discussionmentioning
confidence: 63%
“…In particular, the frontostriatal syndrome does not predict PDD, whereas PC syndrome does. 42 43 In this context, some biomarkers could help us to understand the origin of these complications in patients with PD, 30 41 44 45 46 but we did not detect differences in the SB analysis. Although previous studies found that SCC were an independent predictor of MCI development in CN patients with PD, 10 11 47 only persistent SCC were associated with CI in our study when no other covariates were considered.…”
Section: Discussionmentioning
confidence: 63%
“…Lee et al (2014) identified RNFL thinning among the PD subgroups, and noted that RNFL thickness is thinnest in groups without dementia, suggesting RNFL thinning was associated with the occurrence of VH in PD. Similarly, a recent report confirmed the relationship between RNFL thinning and the presence of VH, revealing that individuals with VH had a thinner GCL-IPL than individuals without VH (Visser et al, 2020). It is believed that the old age, disease's duration, motor disorders, and other non-motor disturbances could worsen the VH as the risk factors in PD (Fénelon et al, 2000;Zhu et al, 2013).…”
Section: Visual Hallucinationsmentioning
confidence: 77%
“…Evidence has demonstrated a significant positive correlation between lower visual acuity and thinning RNFL thickness (Satue et al, 2017;Visser et al, 2020;Abd Hamid et al, 2021; Table 3). Sparkly, the thinness in the ganglion cell-inner plexiform layer in PD was strongly correlated with low contrast visual acuity via a comprehensive battery of visual function tests (Murueta-Goyena et al, 2019;Marrocco et al, 2020).…”
Section: Visual Acuitymentioning
confidence: 99%
See 1 more Smart Citation
“…We also could not find a correlation between IPL thickness and cognition. However, a few previous publications reported a significant correlation between the GCL-IPL and MoCA [53,54]. One longitudinal study reported an increased risk of cognitive decline after three years of follow-up of PD patients with a lower RNFL and GCL-IPL thickness at baseline [53].…”
Section: Correlation Analysesmentioning
confidence: 99%